Improving Speaking Skills of Linguistic Faculty Students through Task-based Instruction at Uzbekistan State World Languages University (Eurasian Journal of Learning and Academic Teaching, 2022)
This study aimed at to improve speaking skills through task-based approach of linguistic faculty students of Uzbekistan State World Languages University. This study was classroom action research and the subjects were 20 students of a linguistic faculty. The techniques for collecting data were observation, task and documentation. The instruments used for data collection were speaking assessment criterion, a list of students, topic-specific written reviews and speaking performance. The result of the study showed that task-based approach could improve speaking skills of teacher-learners at Uzbekistan State World Languages university if implemented correctly.